2013
DOI: 10.1111/desc.12018
|View full text |Cite
|
Sign up to set email alerts
|

The cradle of causal reasoning: newborns’ preference for physical causality

Abstract: Perception of mechanical (i.e. physical) causality, in terms of a cause-effect relationship between two motion events, appears to be a powerful mechanism in our daily experience. In spite of a growing interest in the earliest causal representations, the role of experience in the origin of this sensitivity is still a matter of dispute. Here, we asked the question about the innate origin of causal perception, never tested before at birth. Three experiments were carried out to investigate sensitivity at birth to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 30 publications
2
62
0
1
Order By: Relevance
“…As a result, causal information and associated words were more readily and fully encoded (Craik, Govoni, Naveh-Benjamin, & Anderson, 1996;Uncapher & Rugg, 2005). This possibility is consistent with evidence that infants attend more to causal than non-causal events (Mascalzoni, Regolin, Vallortigara, & Simion, 2013). Young children are also particularly interested in learning about causal properties of objects.…”
Section: Introductionsupporting
confidence: 80%
“…As a result, causal information and associated words were more readily and fully encoded (Craik, Govoni, Naveh-Benjamin, & Anderson, 1996;Uncapher & Rugg, 2005). This possibility is consistent with evidence that infants attend more to causal than non-causal events (Mascalzoni, Regolin, Vallortigara, & Simion, 2013). Young children are also particularly interested in learning about causal properties of objects.…”
Section: Introductionsupporting
confidence: 80%
“…El razonamiento sobre la causalidad física, es decir, la apreciación de la interacción entre dos eventos en términos de las relaciones causa-efecto ha tenido un rol central en la comprensión del mundo físico (Mascalzoni, Regolin, Vallortigara y Simion, 2013). El razonamiento causal, según Atance, Metcalf, Martin-Ordas y Walker (2014), está ya presente en el razonamiento de menores de tres años sobre el mundo físico bajo el "principio de prioridad", el cual establece que las causas de las acciones o fenómenos preceden a sus consecuencias.…”
Section: Breve Referencia Teóricaunclassified
“…In sum, the set of studies reported by Mascalzoni et al (2013) falls short of demonstrating the existence of an innate ability to represent causal relations. The use of preference as a measure is problematic in that it remains unclear how a simple visual preference provides a measure of causal perception.…”
Section: Causal Perception In Newborns?mentioning
confidence: 92%
“…Another way to determine whether causal perception is innate in origin, however, is to look for evidence that newborns can reliably discriminate between causal and non-causal events. In the only study to examine causal perception at birth, Mascalzoni, Regolin, Vallortigara, and Simion (2013) Experiment 2 presented infants with a direct and delayed launching event side-by-side.…”
Section: Causal Perception In Newborns?mentioning
confidence: 99%
See 1 more Smart Citation